Determination of the modes of action and synergies of xylanases by analysis of xylooligosaccharide profiles over time using fluorescence‐assisted carbohydrate electrophoresis. Issue 12 (10th May 2016) - Gong, Weili; Zhang, Huaiqiang; Tian, Li; Liu, Shijia; Wu, Xiuyun; Li, Fuli; Wang, Lushan
Abstract : The structure of xylan, which has a 1, 4‐linked β‐xylose backbone with various substituents, is much more heterogeneous and complex than that of cellulose. Because of this, complete degradation of xylan needs a large number of enzymes that includes GH10, GH11, and GH3 family xylanases together with auxiliary enzymes. Fluorescence‐assisted carbohydrate electrophoresis (FACE) is able to accurately differentiate unsubstituted and substituted xylooligosaccharides (XOS) in the heterogeneous products generated by different xylanases and allows changes in concentrations of specific XOS to be analyzed quantitatively. Based on a quantitative analysis of XOS profiles over time using FACE, we have demonstrated that GH10 and GH11 family xylanases immediately degrade xylan into sizeable XOS, which are converted into smaller XOS in a much lower speed. The shortest substituted XOS produced by hydrolysis of the substituted xylan backbone by GH10 and GH11 family xylanases were MeGlcA 2 Xyl3 and MeGlcA 2 Xyl4, respectively. The unsubstituted xylan backbone was degraded into xylose, xylobiose, and xylotriose by both GH10 and GH11 family xylanases; the product profiles are not family‐specific but, instead, depend on different subsite binding affinities in the active sites of individual enzymes. Synergystic action between xylanases and β‐xylosidase degraded MeGlcA 2 Xyl4 into xylose and MeGlcA 2 Xyl3 but further degradation of MeGlcA 2 Xyl3 required additional enzymes. Synergy between xylanases and β‐xylosidase was also found to significantly accelerate the conversion of XOS into xylose.